Altitude-specific neurocritical care: A case study in the management of traumatic brain injury - Maldonado-Coronel, Fausto (2025)
Introduction: This case illustrates a unique challenge in neurocritical care at high altitude, where sea-level ventilation protocols can be detrimental. It adds novel clinical evidence by showing the pathophysiological consequences and therapeutic reversal of hypercapnia-induced cerebral hyperemia in a high-altitude native with traumatic brain injury (TBI). Main symptoms and findings: A 25-year-old man, lifelong resident at 3600 m above sea level (m.a.s.l.), presented with moderate-to-severe TBI following a motor vehicle accident. He exhibited cerebral edema and hemorrhagic contusions on CT, with transcranial Doppler indicating cerebral hyperemia. Diagnosis, intervention, and outcomes: Initial ventilation based on sea-level PaCO₂ norms led to iatrogenic hypercapnia and cerebral hyperemia. Upon adjusting the ventilatory targets to an altitude-appropriate PaCO₂ range (26–28 mmHg), cerebral blood flow normalized, as confirmed by Doppler. The patient rapidly recovered and was discharged neurologically intact. Conclusion: In high-altitude settings, standard ventilation protocols may provoke secondary cerebral complications. This case highlights the critical importance of individualized, altitude-specific neurocritical strategies, with transcranial Doppler serving as a valuable bedside guide to optimize outcomes in altitude-acclimatized TBI patients.